Peran Kepemimpinan Kiyai Abd Mukti Dalam Mewujudkan Stabilitas Spiritual Anggota Muslimatan Di Pasean Pamekasan - Siti Nazifah; Yanto Yanto; Ahmad Wahyudi (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
The kiai's leadership role is the activity of a kiai in behaving, directing, deciding, and making policies in a formal or informal organization in society. This study attempts to describe the leadership of kiyai Abd Mukti to the Muslim community in the community's spiritual search. Research with a field-related approach, and also some literature. With data collection techniques of observation, interviews, and documentation. The results of the study: the leadership of the kyai who tends to be democratic in their leadership practices is colored with efforts to realize effective human beings. In his leadership, he is not only limited to leading but also directs his mind and energy to achieve a goal, with his patience he leads the Muslim community with the values of life in it. Such leadership will naturally be an example for the community, especially for Muslim members in spiritual matters. The author hopes that this research will contribute to the theory that will be applied. In today's times it is very important for women to become empowered through the Muslim community.